Implicit Queries (IQ) For Contextualized Search - Dumais, Susan; Cutrell, Ed; Sarin, Raman; Horvitz, Eric (SIGIR '04: Proceedings of the 27th annual international ACM SIGIR conference on Research and development in information retrieval, 2004)
The Implicit Query (IQ) prototype is a system which automatically generates context-sensitive searches based on a user’s current computing activities. In the demo, we show IQ running when users are reading or composing email. Queries are automatically generated by analyzing the email message, and results are presented in a small pane adjacent to the current window to provide peripheral awareness of related information.